Boundary Value Problem of Nonlinear Hybrid Differential Equations with Linear and Nonlinear Perturbations - Said Melliani; Abdelati El Allaoui; Lalla Saadia Chadli (International Journal of Differential Equations)
The aim of this paper is to study a boundary value problem of the hybrid differential equation with linear and nonlinear perturbations. It generalizes the existing problem of second type. The existence result is constructed using the Leray–Schauder alternative, and the uniqueness is guaranteed by Banach’s fixed-point theorem. Towards the end of this paper, an example is provided to illustrate the obtained results.